Handbook of Human Factors in Air Transportation Systems - Landry, Steven James (Boca Raton, FL : CRC Press, 2017)
"One of the primary applications of human factors engineering is in the aviation domain, and the importance of human factors has never been greater as U.S. and European authorities seek to modernize the air transportation system through the introduction of advanced automation. This handbook provides regulators, practitioners, researchers, and educators a comprehensive resource for understanding and applying human factors to air transportation."--Provided by publisher.
chapter 1 Operational Details of the Air Transportation System / Steven J. Landry -- chapter 2 The Design of the Flight Deck / Lisa C. Thomas -- chapter 3 The Design of the Air Traffic Control System / Michael Nolan -- chapter 4 Maintenance / William L. Rankin Bill Johnson -- chapter 5 Distributed Work in the National Airspace System -- Traffic Flow Management and Airline Operations Control / Philip J. Smith Ellen J. Bass -- chapter 6 Accident Investigation / William J. Bramble -- section I Operations and Design -- chapter 7 An Overview of Flight Deck Human Factors in the U.S. Aviation Regulatory System / Kathy Abbott -- chapter 8 Certification of Aircraft and Aircraft Systems / Robert E. Joslin -- chapter 9 Safety Systems and Practices / Alan Stolzer -- chapter 10 Security / Douglas Harris -- section II Regulations and Certification -- chapter 11 Data Sources and Research Tools for Human Factors / Mark Wiggins Shayne Loft Johanna Westbrook -- chapter 12 Flight Deck Human Factors / Michelle Yeh Thomas R. Chidester Thomas E. Nesthus -- chapter 13 Situation Awareness in Air Traffic Control / Kim-Phuong L. Vu Dan L. Chiappe -- chapter 14 Error in Air Transportation / Cees Jan Meeuwis Sidney W. A. Dekker -- chapter 15 The Systems Perspective in Air Transportation / Lance Sherry -- section III Research and Development -- chapter 16 A Personal Journey in the Design and Management of the Growing Airspace / Guy André Boy -- chapter 17 Remotely Piloted Aircraft / Alan Hobbs -- section IV The Future.
Keywords: Aerospace Engineering; ENGnetBASE; ERGONOMICSnetBASE; GENERALENGINEERINGnetBASE; MechanicalEngineeringnetBASE; Product Design; SCI-TECHnetBASE; STMnetBASE; Systems & Control Engineering